Development of ambient storable meal for calamity victims and other targets employing radiation processing and evaluation of its nutritional, organoleptic, and safety parameters. (June 2016) - Kumar, Sanjeev; Saxena, Sudhanshu; Verma, Jyoti; Gautam, Satyendra
Abstract: During natural calamities nutritious, safe, and ambient storable meal is issue of immense concern. Recently Joint FAO/IAEA programme of nuclear techniques in Food and Agriculture has undertaken Coordinated Research Project (CRP) where a product 'S tuffedB akedF ood (SBF)' was developed in India. SBF consists of partially fermented multigrain dough enriched with 5% saturated fat and stuffed with flour of roasted chick pea; boiled and peeled potato (mashed); and cooked chick pea split (mashed) with spices and salt. Stuffed lobe was convection baked, vacuum packaged and gamma irradiated (15 kGy). The product was well acceptable after prolonged storage at ambient temperature while retaining its quality attributes. SBF can also be useful for other targets like defence personnel, school lunch programme, expeditions, and astronauts. Mutation analyses in models including human TK6 lymphoblast cell line at genes tk +/− and hprt + ; and bacterial systems [ Escherichia coli MG1655 cells ( rpoB gene); and Ames strains (TA 100 and TA 102)] endorsed its genotoxic safety. Highlights: Under IAEA-CRP, a meal was developed for calamity victims and other targets. Developed food was ambient storable up to 8 months upon irradiation. Nutritional, antioxidant and sensory qualities of irradiated SBF were retained. Irradiated SBF was not found to display any genotoxicity in different models.